Bullous. Emphysema and surgery. - Delbene, Roberto; González, Roberto; Rodríguez, Ariel; Rivas, Carlos; Martínez, José L (Cirugía del Uruguay, 1989)
Authors make a retrospectiva analysis of emphysematous vesicles carriers who were operated on in the Chest Surgery Service of Hospital Saint Bois between 1960 and 1980.